Checklist of native freshwater fish from Surabaya River, Indonesia - ABDUL R. FAQIH; RR. JUNI TRIASTUTI; DITA WISUDYAWATI; SEPTI ANITASARI; VIOL D. KHARISMA; RAHMI RAHAYU; HERI CAHYONO; JILA SULIASTINI; R. ADHARYAN ISLAMY; FITRI S. VALEN; MUHAMMAD B. TAMAM; PRIGI ARISANDI; JOSIE SOUTH; AHMAD S. KAMARUDIN; ALIFA K. WIJAYA; VERYL HASAN (Society for Indonesian Biodiversity, 2026)
Abstract. Faqih AR, Triastuti RRJ, Wisudyawati D, Anitasari S, Kharisma VD, Rahayu R, Cahyono H, Suliastini J, Islamy RA, Valen FS, Tamam MB, Arisandi P, South J, Kamarudin AS, Wijaya AK, Hasan V. 2026. Checklist of native freshwater fish from Surabaya River, Indonesia. Biodiversitas 27 (3): d270327. https://doi.org/10.13057/biodiv/d270327. Surabaya River is a tributary of the Brantas River and is habitat to several freshwater fish species. The aim of this study was to provide information on the species composition of freshwater fish in the Surabaya River, one of the most important rivers in East Java, Indonesia. All samples used in this study were caught from December 25, 2025, to January 25, 2026. Sampling was conducted at three stations on the Surabaya River: the starting point of the bifurcation at Mlirip Sluice Gate, Mojokerto Regency (Station 1); Krian Sub-District, Sidoarjo Regency (Station 2); and the end of the river at Jagir Sluice Gate, Surabaya City (Station 3). Specimens were identified using specialized papers and books. This work recorded 35 fish species across 31 genera and 17 families. Cyprinidae was the dominant family, comprising 10 genera and 11 species. Station 1 had the highest species richness (34 species), while Station 3 had the lowest (17 species). Several species endemic of Java, such as Java walking catfish Clarias batrachus, Asian redtail catfish Hemibagrus nemurus, wrestling halfbeak Dermogenys pusilla, and spotted barb Barbodes binotatus, were found in this study, indicating that further attention is needed to preserve their habitat. The new information on freshwater fish diversity across different parts of the river will be useful for updating the current database on Javanese freshwater fish species diversity and for providing an updated native species inventory for three segments during the 2025-2026 sampling. Information on the habitat use and ecological interactions of fish occurring in the Surabaya River is urgently needed to make appropriate conservation decisions and plans.